2016
DOI: 10.1093/jxb/erw047
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between ethylene, gibberellins, and brassinosteroids in the development of rhizobial and mycorrhizal symbioses of pea

Abstract: HighlightAn ethylene-insensitive mutant of pea with enhanced nodulation and arbuscular mycorrhizal development showed that gibberellin and brassinosteroid deficiency affect nodule number via ethylene levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 67 publications
(125 reference statements)
2
60
0
1
Order By: Relevance
“…ABA-related gene expression patterns indicated that the positive influence exerted by the mycorrhizal colonization on ABA biosynthesis and signaling (Herrera-Medina et al, 2007;Martín-Rodríguez et al, 2016), was not affected in the spr2 mutant. On the other hand, ET gene expression patterns concurred with ample evidence proposing that ET generally has an inhibitory effect on the AMF colonization (Foo et al, 2013(Foo et al, , 2016Pozo et al, 2015;Gomez Monteiro Fracetto, Pereira Peres & Rodriguez Lambais, 2017). Thus, the majority of the ET biosynthetic and signaling genes analyzed were induced in mycorrhizal spr2 roots, predominantly at 32 dpi.…”
Section: Ion Identitysupporting
confidence: 61%
See 1 more Smart Citation
“…ABA-related gene expression patterns indicated that the positive influence exerted by the mycorrhizal colonization on ABA biosynthesis and signaling (Herrera-Medina et al, 2007;Martín-Rodríguez et al, 2016), was not affected in the spr2 mutant. On the other hand, ET gene expression patterns concurred with ample evidence proposing that ET generally has an inhibitory effect on the AMF colonization (Foo et al, 2013(Foo et al, , 2016Pozo et al, 2015;Gomez Monteiro Fracetto, Pereira Peres & Rodriguez Lambais, 2017). Thus, the majority of the ET biosynthetic and signaling genes analyzed were induced in mycorrhizal spr2 roots, predominantly at 32 dpi.…”
Section: Ion Identitysupporting
confidence: 61%
“…BR-related genes were strongly repressed in mycorrhizal WT roots, while they were generally up-regulated in mycorrhizal spr2 roots. This was also in contradiction with the overall positive influence that BRs had in various plant models, including tomato (Bitterlich et al, 2014a(Bitterlich et al, , 2014bFoo et al, 2016;Tofighi et al, 2017). However, most of this information was obtained using BR-deficient mutants under experimental conditions that may have influenced other plant hormones (e.g., ethylene; Jiroutova, Oklestkova & Strnad, 2018), known to affect mycorrhizal colonization.…”
Section: Ion Identitymentioning
confidence: 89%
“…Ethylene signaling is a key regulator of rhizobia infection and nodule organogenesis, as mutants in Ein2 are hypernodulating and hyperinfected (Penmetsa and Cook, 1997;Penmetsa et al, 2008;Foo et al, 2016).…”
mentioning
confidence: 99%
“…Previously, more nodules of smaller size were observed in the Mm SWRI9‐inoculated association than in Mc CP‐31‐inoculated association during low‐Pi supply, which coincided with lower SNF capacity of Mm SWRI9‐inoculated plants than that of the Mc CP‐31‐inoculated plants under Pi‐deficient conditions (Nasr Esfahani et al ., ). It has recently been reported that the pea ( Pisum sativum ) ethylene (ET)‐insensitive and gibberellin (GA)‐deficient double mutant ein2 na and ET‐insensitive and brassinosteroid (BR)‐deficient double mutant ein2 lk produced more nodules of smaller size compared with wild‐type plants (Foo et al ., ). Our RNA‐seq data analysis revealed differential expression patterns of hormone‐related genes obtained from Mm SWRI9‐Pd/ Mm SWRI9‐Ps and Mc CP‐31‐Pd/ Mc CP‐31‐Ps comparisons (Figure S1).…”
Section: Resultsmentioning
confidence: 97%